Analisis Operasional Receiving Dalam Meningkatkan Kualitas Bahan Perishable Di Hotel Four Points By Sheraton Batam - Carel, Christoper; Tondang, Bahagia; Kamal, Mustafa (Politeknik Pariwisata Medan, 2023)
Receiving Departement is a department that handles the receipts of goods that have been ordered by Purchasing Departement, especially the receipt of perishable material. The goal of this study is to understand the typical method used by the Four Points By Sheraton Batam receiving department for receiving perishable commodities, as well as the typical way that procedure is used across the hotel. Researchers employed interviews, observations, and literature reviews as data gathering techniques for this sort of study. They also used the descriptive qualitative research approach. The Four Points by Sheraton Batam Hotel's procedure for receiving perishable commodities is the study's outcome. where materials from suppliers are sent to the hotel and received by the receiving personnel. Subsequently, the materials are inspected, examined, and matched against the Purchase Order (PO). The inspection conducted by the receiving personnel includes checking both the quality and quantity of the materials. The supplier's invoice will be signed by the receiving personnel after this process. Following that, the perishable materials will be distributed to the requesting users.